Transapical transcatheter aortic valve replacement in patients with or without prior coronary artery bypass graft operation. Issue 1 (December 2016) - Voudris, Konstantinos; Wong, S.; Kaple, Ryan; Kampaktsis, Polydoros; de Biasi, Andreas; Weiss, Jonathan; Devereux, Richard; Krieger, Karl; Kim, Luke; Swaminathan, Rajesh; Feldman, Dmitriy; Singh, Harsimran; et al.
Abstract Background Transapical approach (TA) is an established access alternative to the transfemoral technique in patients undergoing transcatheter aortic valve replacement (TAVR) for treatment of symptomatic aortic valve stenosis. The impact of prior coronary artery bypass grafting (CABG) on clinical outcomes in patients undergoing TA-TAVR is not well defined. Methods A single center retrospective cohort analysis of 126 patients (male 41%, mean age 85.8 ± 6.1 years) who underwent TA balloon expandable TAVR (Edwards SAPIEN, SAPIEN XT or SAPIEN 3) was performed. Patients were classified as having prior CABG (n  = 45) or no prior CABG (n  = 81). Baseline clinical characteristics, in-hospital, 30-day, 6 months and one-year clinical outcomes were compared. Results Compared to patients without prior CABG, CABG patients were more likely to be male (62.2 vs. 29.6%, p  < 0.001) with a higher STS score (11.66 ± 5.47 vs. 8.99 ± 4.19, p  = 0.003), history of myocardial infarction (55 vs. 21.1%, p  < 0.001), implantable cardioverter defibrillator (17.8 vs. 3.7%, p  = 0.017), left main coronary artery disease (42.2 vs. 4.9%, p  < 0.001), and proximal left anterior descending coronary artery stenosis (57.8 vs. 16%, p  < 0.001). They also presented with a lower left ventricular ejection fraction (%) (42.3 ± 15.3 vs. 54.3 ± 11.6, p  < 0.01) and a larger effective valve orifice area (0.75 ± 0.20 cm2 vs. 0.67 ± 0.14 cm2, p  = 0.025). There were no intra-procedural deaths, no differences in stroke (0 vs. 1.2%, p  = 1.0), procedure time in hours (3.50 ± 0.80 vs. 3.26 ± 0.86, p  = 0.127), re-intubation rate (8.9 vs. 8.6%p  = 1.0), and renal function (highest creatinine value 1.73 ± 0.71 mg/ml vs.1.88 ± 1.15 mg/ml, p  = 0.43). All-cause mortality at 6 months was similar in both groups (11.4, vs. 17.3%p  = 0.44), and one-year survival was 81.8 and 77.8% respectively (p  = 0.51). On multivariate analysis, the only factor significantly associated with one-year mortality was prior history of stroke (HR, 2.76; 95% CI, 1.06-7.17, p  = 0.037). Conclusion Despite the higher baseline clinical risk profile, patients with history of prior CABG undergoing TA-TAVR had comparable in-hospital, 6 months and one-year clinical outcomes to those without prior CABG.